Tail risk connectedness and portfolio management between energy tokens and FinTech stocks: evidence from quantile-based approaches - Sania Ashraf; Mohammad Abdullah; Skander Slim; Shruti R. (Cogent Economics & Finance)
This study investigates the tail risk connectedness between energy tokens and FinTech stocks, two blockchain-enabled yet sectorally distinct asset classes. Using data from September 2018 to August 2023, we examine five energy tokens and five FinTech indices through the CAViaR model and the quantile coherency framework, capturing interdependencies under extreme market conditions, including COVID-19 and the Russia-Ukraine war. Our findings reveal generally weak connectedness between energy tokens and FinTech indices, suggesting strong diversification potential under normal conditions. However, tail risk interconnectedness intensifies during crises, with some tokens acting as safe havens while others amplify downside risks. Portfolio analysis highlights that diversification benefits and optimal hedging strategies vary by market regime and investment horizon, TSL and ELEC provide short-term protection, while SNC and ROX offer long-term stability. By shifting focus from traditional return-volatility spillovers to tail risk dynamics, this study provides a robust framework for assessing financial contagion and resilience. Hence, our findings offer actionable insights for investors, portfolio managers, and policymakers seeking to construct resilient portfolios using energy tokens and FinTech stocks.